1990
DOI: 10.1111/j.1440-1827.1990.tb01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric and Intestinal Phenotypic Expression of Human Stomach Cancers as Revealed by Pepsinogen lmmunohistochemistry and Mucin Histochemistry

Abstract: Gastric and intestinal phenotypic expression in 223 surgically obtained primary gastric cancers and their histogenetic relationship to intestinal metaplasia in the surrounding gastric mucosa were studied by mucin histochemistry and pepsinogen (Pg) immunohistochemistry. Histochemical differentiation of mucins (paradoxical concanavalin A, the galactose oxidase‐Schiff sequence and sialidase galactose oxidase Schiff) and immunohisto chemical staining of Pgs I and II, allowed differentiation of gastric cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
177
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(189 citation statements)
references
References 19 publications
10
177
2
Order By: Relevance
“…b P ¼ 0.0493 (advanced adenocarcinoma of the gastric cardia vs advanced adenocarcinoma of the distal stomach) and P ¼ 0.0363 (total adenocarcinoma of the gastric cardia vs total adenocarcinoma of the distal stomach). Table 5 Genetic alterations in differentiated-type adenocarcinoma of the gastric cardia and distal stomach whereas I-phenotype tumours have been reported to account for 10.1% of all undifferentiated-type tumours (Tatematsu et al, 1990;Egashira et al, 1999;Tajima et al, 2001aTajima et al, , b, 2004Yamazaki et al, 2006). These previous data suggest that gastric carcinomas may arise from various types of gastric mucosa, although differentiatedtype tumours have generally been considered to arise from gastric mucosa with intestinal metaplasia and undifferentiated-type tumours to arise from ordinary gastric mucosa without intestinal metaplasia (Lauren 1965;Nakamura et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…b P ¼ 0.0493 (advanced adenocarcinoma of the gastric cardia vs advanced adenocarcinoma of the distal stomach) and P ¼ 0.0363 (total adenocarcinoma of the gastric cardia vs total adenocarcinoma of the distal stomach). Table 5 Genetic alterations in differentiated-type adenocarcinoma of the gastric cardia and distal stomach whereas I-phenotype tumours have been reported to account for 10.1% of all undifferentiated-type tumours (Tatematsu et al, 1990;Egashira et al, 1999;Tajima et al, 2001aTajima et al, , b, 2004Yamazaki et al, 2006). These previous data suggest that gastric carcinomas may arise from various types of gastric mucosa, although differentiatedtype tumours have generally been considered to arise from gastric mucosa with intestinal metaplasia and undifferentiated-type tumours to arise from ordinary gastric mucosa without intestinal metaplasia (Lauren 1965;Nakamura et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] By sequential observation of rat glandular stomach carcinomas and comparisons of phenotypic expression of human gastric carcinoma cells between early and advanced cases, a phenotypic shift from gastric to intestinal epithelial cell type expression has been recognized with progression of each histological type of gastric carcinomas. [33][34][35][36] The present results regarding phenotypic expression of tumor cells showed that mouse glandular stomach adenomas and carcinomas consist solely of tumor cells of gastric epithelial cell type, without any intestinal metaplasia in the mucosa surrounding carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown [2][3][4][5] that human and rat gastric cancer cells of different histologic types can be classified into 2 categories: a gastric epithelial cell type, comprising pyloric gland cells and surface mucous cells, and an intestinal epithelial cell type, comprising goblet cells and intestinal absorptive cells, based on our recent results obtained by mucin histochemistry [paradoxical concanavalin A (Con A), galactose oxidase Schiff (GOS), and sialidase-GOS staining] and enzyme immunohistochemistry [pepsinogen staining].…”
mentioning
confidence: 99%
“…In contrast, no ALP was detectable in normal gastric mucosae except for the I-ALP activity in intestinal metaplasias. We have reported 16) relatively low contents of ALPs in 13 out of 38 human primary signet-ring cell carcinomas. Other authors 6,17) have also demonstrated a low level of ALP expression in various human gastric carcinomas.…”
mentioning
confidence: 99%